Guided Qur’an Learning Using the Ummi Method: Building Fluency and Spiritual Engagement - Mas'odi, Mas'odi; Amin, Moh. Makinul; AR, Samsul (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2025)
The Qur’an was revealed in the Arabian Peninsula using the Arabic language; therefore, learning Arabic is essential to read, understand, and apply its teachings effectively. This study explores the use of the Ummi Method in Qur’anic learning at Sekolah Rendah Islam Al-Falah Bestari, Malaysia. The Ummi Method is a structured approach to reading the Qur’an that emphasizes tartil (measured recitation) based on tajwid principles and adopts a mother-tongue approach rooted in affection and empathy. It employs a combination of classical read-listen activities and a quality assurance system involving tashih (correction), tahsin (refinement), and teacher certification. The study focuses on three key quality aspects: qualified methodology, competent teachers, and a reliable system. Using a participatory observation method, the researcher directly engaged in classroom learning within a short research period. The findings revealed that many students initially struggled with correct recitation and memorization despite recognizing Arabic letters. However, after applying the Ummi Method, there was a noticeable improvement in their reading accuracy, fluency, and memorization of short surahs. This research contributes to strengthening Qur’anic pedagogy by demonstrating that the Ummi Method effectively enhances students’ motivation, comprehension, and spiritual connection through a systematic, affectionate, and quality-based learning framework